Innovative Pedagogy in Arabic Language Acquisition: The Al-Karmaji Approach - Farikha, Nurul; Fauji, Imam (Indonesian Journal of Islamic Studies, 2024)
This study employs a qualitative, descriptive approach to investigate the comprehensive learning process of the Arabic textbook, al-karmaji, in a high school X class at eLKISI Mojokerto. The research delves into planning, methodology, strategies, and utilized media, encompassing stages of initiation, core activities, and conclusion assessments. Findings reveal a unique pedagogical method relying on training from the book's author or designated teacher rather than traditional syllabi or lesson plans. Learning activities adopt a humanistic approach coupled with the qowaid wa tar method, integrating motivational techniques and gamification. Notably, assessments occur weekly and tri-monthly. The study underscores the transformative potential of the al-karmaji approach in Arabic language instruction. Highlight: Innovative Pedagogy: This study introduces a unique pedagogical approach in Arabic language instruction, emphasizing experiential learning over conventional lesson plans. Humanistic Learning: The research highlights the incorporation of a humanistic approach alongside the qowaid wa tar method, enhancing student engagement and motivation in the learning process. Assessment Frequency: The study identifies a structured assessment schedule, conducted weekly and tri-monthly, providing continuous feedback and opportunities for student progress tracking. Keyword: Arabic Language Instruction, Al-Karmaji Textbook, Qualitative Research, Pedagogical Approach, Learning Assessment